The generosity effect: Fairness in sharing gains and losses - Guillermo Baquero; Willem Smit; Luc Wathieu (European School of Management and Technology (ESMT), 2013)
We explore the interaction between fairness attitudes and reference dependence both theoretically and experimentally. Our theory of fairness behavior under reference-dependent preferences in the context of ultimatum games, defines fairness in the utility domain and not in the domain of dollar payments. We test our model predictions using a within-subject design with ultimatum and dictator games involving gains and losses of varying amounts. Proposers indicated their offer in gain- and (neatly comparable) loss- games; responders indicated minimum acceptable gain and maximum acceptable loss. We find a significant generosity effect in the loss domain: on average, proposers bear the largest share of losses as if anticipating responders' call for a smaller share. In contrast, reference dependence hardly affects the outcome of dictator games -where responders have no veto right- though we detect a small but significant compassion effect, whereby dictators are on average somewhat more generous sharing losses than sharing gains.
urn:nbn:de:101:1-2013091111545
Keywords: D03; D81; 650; Fairness; loss domain; ultimatum game; dictator game; referencedependent preferences; social preferences